Two Cases, One Good Therapist - Karlin, Robert A. (Pragmatic Case Studies in Psychotherapy, 2006)
In my view, the most important similarity between Betty and Lawrence is that they had the same therapist, not that they had similar problems (Hamburg, 2006). This view raises several issues. First, are there any aspects of what Dr. Hamburg does that might be problematic for a less experienced and talented therapist. The one thing that clearly falls in this category is his use of the videotape metaphor for discovering memories during hypnotic age regression. This metaphor has created difficulties in the past and might best be avoided. Second, Dr. Hamburg seems to rely more on personally invented procedures and clinical lore than on manualized, evidence-based techniques. In this paper, the evidence base for evidence-based procedures is examined in terms of what we know about effect sizes from research on clinical hypnosis. I suggest that the evidence base for most evidence-based procedures is, at best, weak. Third, I speculate briefly about the effects of training clinical psychology graduate students in cognitive-behavioral therapy (CBT) by having them serve as therapists in randomized control trials (RCTs). In contrast to my previously stated (relatively positive) views (Karlin, 2002), I suggest that such training may not aid them in becoming thoughtful, creative, flexible therapists like Dr. Hamburg.